Fermentation Tofu Using Consortium Lactic Acid Bacteria Isolated from Whey Tofu as Biocoagulant and Bioperservation - Siti Eka Yulianti (ANNALES BOGORIENSES, 2021)
Tofu is a traditional food that has high protein content and is prone to spoilage. A fermentation process with consortium lactic acid bacteria (LAB) that can produce bacteriocin has is carried out to get tofu that is more durable with better taste.  The Bacteria which are used in this study are Lactobacillus fermentum, Leuconostoc mesenteroides, and Lactobacillus plantarum.  L. fermentum is isolated from whey tofu. The antibacterial ability of each bacteria is measured by bacteriocins assay after incubation at 0 hours; 4 hours; and 8 hours in a row are L. fermentum 0; 2506.429 AU/mL; 1502.679 AU/mL;  L. mesenteroides 0 AU/mL; 2506.43 AU/mL; 2939.44 AU/mL; L. plantarum 760.39 AU/mL; 3341.25 AU/mL; 3889.29 AU/mL. Ratio inoculum bacteria (a:b:c) which are used are 2:1:1, 1:1:2, and 1:1:1 by using percentage of inoculum 10%. The Optimum inoculum age of these bacterium is 6 hours with µmax each bacteria in a row is 0.04 h-1, 0.02 h-1, dan 0.02 h-1. The fermentation is processed in 8 hours at 37ᵒC of temperature without agitation. From this optimation, the highest bacteriocin activity in tofu curd is 1767.857 AU/mL, which is in a ratio of 1:1:2 at the 4th hour.